Analisis Pengaruh Wilayah Kerja Dan Tunjangan Jabatan Terhadap Kinerja Perangkat - Ahmad Jaelani (Jurnal Strategi Bisnis Teknologi, 2024)
The performance of equipment, especially in sub-district areas, is a strategic issue because improving bureaucratic performance has broad implications. A study of the performance of local governments, especially those involved in providing public services, has strategic value. Information regarding bureaucratic performance and the factors that shape bureaucratic performance is of course important to know so that policies to improve bureaucratic performance can be formulated. By improving performance, it is hoped that it can improve the level of public trust in the government. Furthermore, to analyze device performance requires some kind of performance measurement device based on balanced results to measure success in meeting goals and objectives. Therefore, a number of indicators are needed to assess performance. Performance measurement is a useful tool in efforts to achieve goals. Through performance measurement, an assessment process can be carried out regarding the achievement of predetermined goals and performance measurement can provide an objective assessment in making management decisions. Apart from that, through performance measurement, the success of a government agency can be seen from the agency's capabilities, based on the resources it manages in accordance with the plans that have been prepared.